Os cursos de Pedagogia da Universidade Estadual Paulista e a Educação Inclusiva - Fonseca-janes, Cristiane Regina Xavier; Omote, Sadao [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2013)
Inclusive education is seen as quality education that should be provided by the educational system for all children, young people and adults. In order to put such a proposal into effect, qualified personnel are needed who are equipped to face such a challenge. This paper aims to examine the curriculum matrices of Pedagogy courses of the Universidade Estadual Paulista - UNESP that intend to prepare future teachers to follow an inclusive perspective. To this end, the political-pedagogical projects of six Pedagogy courses, the University resolutions that regulate the courses and excerpts taken from interviews carried out with course coordinators were analyzed. In order to analyze the curriculum matrices, the required subjects were distributed on a table according to the following categories: 1) specific subjects related to inclusive education, 2) number of hours of each subject related to inclusive education, 3) specific subjects related to special education and 4) amount of time scheduled for each subject related to special education. Among the six Pedagogy courses, five had subjects that focused on issues related to inclusive education, with varying time allotments, and four had subjects focusing on specific issues related to special education.

A educação inclusiva é tida como uma educação de qualidade que deve ser oferecida pelo sistema educacional a todas as crianças, jovens e adultos. Para a efetivação de tal proposta, dentre várias necessidades, precisamos de recursos humanos qualificados para o enfrentamento desse desafio. Este trabalho tem por objetivo analisar as matrizes curriculares dos cursos de Pedagogia da Universidade Estadual Paulista para a formação em uma perspectiva inclusiva. Para isto, foram analisados os projetos político-pedagógicos dos seis cursos de Pedagogia, as Resoluções da UNESP que os regulamentam e trechos de entrevistas realizadas com os coordenadores dos respectivos cursos. Para análise das matrizes, as disciplinas obrigatórias foram distribuídas em um quadro com as seguintes categorias: 1) disciplinas específicas relacionadas com a Educação Inclusiva, 2) carga horária das disciplinas relacionadas com a Educação Inclusiva, 3) disciplinas específicas relacionadas com a Educação Especial e 4) carga horária das disciplinas relacionadas com a Educação Especial. Dos seis cursos de Pedagogia da UNESP, cinco possuem disciplinas voltadas para a questão da Educação Inclusiva, com as mais diversificadas cargas horárias, e quatro possuem disciplinas voltadas para questões específicas da Educação Especial.
The courses of Pedagogy at Universidade Estadual Paulista and Inclusive Education
Keywords: Educação Inclusiva; Educação Especial; Grade Curricular; Curso de Pedagogia; Inclusive Education; Special Education; Curriculum; Pedagogy Course